(untitled) - Reynolds, Jason; Ridley, Alison (Atheneum Books for Young Readers, 2025)
Confident in his albino skin, African American Lu prepares to lead the track team to victory while navigating hurdles at home that make him reassess his values.
Keywords: Deportes de pista; Novela juvenil; Fiction; Fiction; African Americans; Conducta de vida; Spanish language materials; Novela juvenil; Afronorteamericanos; Familia; Novela juvenil; Albinos y albinismo; Novela juvenil; Novela juvenil; Albinos and albinism; Juvenile fiction; Pregnancy; Track and field; Fiction; Conduct of life; Family life; Juvenile fiction; Pregnancy; Juvenile fiction; Albinos and albinism; Juvenile fiction; African Americans; Juvenile fiction; Track and field; Fiction; Conduct of life; Juvenile fiction; Fiction; Family life; Fiction; Sports fiction